Investigating Direction of Arrival (DOA) Estimation Techniques with Smart Antennas for Improved Wireless Communication Analysis (International Journal of Food and Nutritional Sciences, 2021)
Within the realm of wireless communication systems, smart antenna systems play a pivotal role. This paper commences with a concise overview of the array correlation matrix in the context of wireless communications. Subsequently, it delves into the significance of Direction of Arrival (DOA) estimation, clarifying its objectives within wireless communication systems. The essence of this paper lies in the in-depth exploration of three distinct DOA estimation techniques: Bartlett DOA estimation, Minimum Variance Distortionless Response (MVDR), and Linear Prediction DOA estimation. Each of these techniques is comprehensively detailed in the fourth section, shedding light on their unique approaches and practical applications. The final section of this paper embarks on a rigorous comparative analysis, evaluating the performance of the aforementioned DOA estimation methods. This evaluation thoroughly examines their individual strengths and limitations, leading to a comprehensive conclusion..